Benzenoid systems with extremal vertex-degree-based topological indices (2014)
In the current chemical literature, a large number of vertex–degree–based topological indices T I are considered, defined as the sum over all edges of the molecular graph of some function Ψ(x, y), where x and y are the degrees of the end-vertices of the respective edge. In order to find the minimal value of T I over benzenoid systems with h hexagons, we characterize convex benzenoid systems W such that ni(W) = ni(Sh), where ni is the number of internal vertices and Sh is the spiral benzenoid system. If such W does exist, then W has minimal T I-value. Otherwise, the spiral Sh has minimal T I-value.